Dictyostelids from Jilin Province, China II - Liu, Pu; Li, Yu (Phytotaxa, 2017)
Four species of dictyostelid cellular slime molds (dictyostelids) in two genera were isolated from forest soil samples collected from Jilin Province in China. Dictyostelium recurvibasicum is new to science. Two of four species (D. longosporum and Polysphondylium tenuissimum) are new to China, and D. brefeldianum is recorded for the first time in the northern part of the country, being known previously only from Taiwan. Descriptions and illustrations are provided herein for these species based on our collections.